Do Foreign Firms Bring Value to Emerging Country? - Johan, Suwinto; Siregar, Hermanto; Santoso, Perdana Wahyu; Maulana, Tubagus Nur Ahmad (Jurnal Manajemen Teknologi, 2012)
Abstract. The aim of the paper is to study the value created by foreign firms in Indonesia finance company industry over the period 2001-2011. We analysed the value creation of foreign firms by comparing the key financial performance to local shareholders. Foreign firms are the major players in banking industry and automotive industry with market share more than 90% in both 2 wheeler and 4 wheeler. Meanwhile, the automotive manufacturers and dealers are the one who provide the products of financing for finance company. We analysed 7 micro key financial ratios (profitability, efficiency, growth, firm size, liquidity, solvency and asset quality). We use non parametric Mann Whitney and parametric panel data dummy regression. The empirical results show that finance companies owned by foreign firms are more efficient, lower in profitability, bigger in size, higher in growth capability, lower in liquidity and higher in solvency.